2005
DOI: 10.1093/her/cyh032
|View full text |Cite
|
Sign up to set email alerts
|

Process evaluation of a store-based environmental obesity intervention on two American Indian Reservations

Abstract: Obesity and other diet-related chronic diseases are widespread in American Indian communities. Inadequate access to healthy food on many reservations has led to a high-fat, high-sugar diet. The purpose of this paper is to report on the results of the process evaluation of a food store-based program to improve diet on two American Indian reservations. Process data were collected from 11 intervention stores to document the implementation of the Apache Healthy Stores (AHS) program. Process evaluation instruments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
93
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(97 citation statements)
references
References 15 publications
3
93
0
1
Order By: Relevance
“…121 Interventions at community corner stores are a relatively new mechanism to affect dietary intake in communities. 122 Programs typically include 1 or several components ranging from infrastructure changes (eg, the addition of refrigeration) to the use of social marketing. Current data suggest that these types of interventions hold promise for shifting shopping habits and knowledge.…”
Section: Community Food Accessmentioning
confidence: 99%
“…121 Interventions at community corner stores are a relatively new mechanism to affect dietary intake in communities. 122 Programs typically include 1 or several components ranging from infrastructure changes (eg, the addition of refrigeration) to the use of social marketing. Current data suggest that these types of interventions hold promise for shifting shopping habits and knowledge.…”
Section: Community Food Accessmentioning
confidence: 99%
“…In response to this fact, a food store-based program was implemented to improve diets on two American Indian reservations (Curran, Gittelsohn, Anliker, Ethelbah, Blake, Sharma, & Caballero, 2005). The Apache Healthy Stores The study reported at the store level, the AHS intervention had a high level of reach, and a moderate to high level of fidelity was stated in terms of promoting food availability and shelf labeling along with posters and educational displays.…”
Section: Nutrition Programs For Native Americansmentioning
confidence: 99%
“…The Curran et al (2005) project was important for learning useful lessons for future programs on other American Indian reservations in rural or urban settings. For instance, greater challenges were reported with smaller stores to stock specific healthier food items such as lower fat milk and fresh fruit than larger stores (Curran et al, 2005).…”
Section: Nutrition Programs For Native Americansmentioning
confidence: 99%
See 2 more Smart Citations